2015
DOI: 10.1007/8904_2015_439
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Chain Acyl-CoA Dehydrogenase Deficiency: Evaluation of Genotype-Phenotype Correlation in Patients Detected by Newborn Screening

Abstract: Background: Medium-chain acyl-CoA dehydrogenase deficiency (MCADD) is included in many newborn screening programmes worldwide. In addition to the prevalent mutation c.985A>G in the ACADM gene, potentially mild mutations like c.199T>C are frequently found in screening cohorts. There is ongoing discussion whether this mutation is associated with a clinical phenotype.Methods: In 37 MCADD patients detected by newborn screening, biochemical phenotype (octanoylcarnitine (C8), ratios of C8 to acetylcarnitine (C2), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 34 publications
6
35
1
1
Order By: Relevance
“…Our study has some limitations. First, we did not analyze mitochondrial DNA and new candidate genes ( NEBL , HADHA , HADHB , and DHCR7 ) associated with hypoparathyroidism . However, mitochondrial disorders and new candidate gene defect–related symptoms were not seen in patients without mutations in our study.…”
Section: Discussionmentioning
confidence: 79%
“…Our study has some limitations. First, we did not analyze mitochondrial DNA and new candidate genes ( NEBL , HADHA , HADHB , and DHCR7 ) associated with hypoparathyroidism . However, mitochondrial disorders and new candidate gene defect–related symptoms were not seen in patients without mutations in our study.…”
Section: Discussionmentioning
confidence: 79%
“…Neonatal triggers were defined as neonatal complications and interventions suggestive of underlying health complications determined by clinician authors as most likely to result in potential MCADD symptoms. Neonatal symptoms were defined by clinician authors as symptoms consistent with MCADD, many based on reports of symptoms manifested in individuals affected with MCADD (9) (14) (15) (16) (17) (18) (19) (20). Neonatal abnormal labs were defined by clinician authors as laboratory test abnormalities of potential concern in the context of MCADD (excluding newborn screening and MCADD diagnostic biochemical and molecular test results).…”
Section: Methodsmentioning
confidence: 99%
“…There is still controversy about the use of L‐carnitine, especially in those with normal C0. Furthermore, mixed or formula feeding might be recommended, given that recent research has shown that exclusively breast‐fed MCADD neonates are at a higher risk for early metabolic decompensation . Also, it has been suggested that patients carry an updated emergency letter containing contact information for the patient's metabolic specialists and a brief discussion of emergency treatment methods …”
Section: Discussionmentioning
confidence: 99%